New model and paradigms of complex formation of competencies in biological disciplines - Kabatayeva, Zhadyra; Bakirova, Kulzhakhan; Bagimbayeva, Zukhra; Kulenova, Gulnara; Missinova, Balzhan (International Journal of Innovative Research and Scientific Studies, 2025)
In this paper, we present a new interpretation of the principles of an integrated approach to the formation of professional competencies of students majoring in biology. The theoretical principles of cognitive multilayering (CMP), dynamic interdisciplinarity (DIF), and cognitive-digital synthesis (CDC) are formulated. Problematic retraction (PIT) and engagement shift (EST) are discussed. The methodological basis for the need to transform from fragmentary pedagogical strategies to the systemic integration of interdisciplinary, cognitive, digital, and project-research components of educational processing has been updated. The methodological foundations of the integrated approach, including the activity paradigm, constructivism, competence model, and elements of digital pedagogy, have been revised. The author's model of the integrated approach, which takes into account the challenges of the modern educational environment and focuses on the development of professional thinking, research, and digital skills of future specialists, is interpreted. The pedagogical productivity of this approach for the formation of holistic and adaptive educational trajectories in natural science training in educational processing in biological disciplines is theoretically substantiated.